Crime Against Women: A Challenge To Women Empowerment - Dr. Chingangbam Newgold Devi; Dr. Achom Roshan kumar; Dr. Kadam Ibotombi Singh (Revista Electronica de Veterinaria, 2024)
Empowerment of women is necessary for the welfare of women and for the development of society. Initiatives are being taken up by the government and many non-governmental organisations to promote women empowerment. Various schemes and programmes are implemented for the welfare of women and to improve their status in the society. However, many crimes against women such as rape, molestation, eve-teasing, honour killing, sexual harassment, female infanticide, female foeticide, dowry, etc. are continuously happening and act as obstacles to the process of empowerment of women. These crimes equally affected the life of women without making any differentiation between educated, uneducated, rural, urban, developed, developing, underdeveloped, working, non-working women and equally make the victims of these crimes. These crimes make many women psychologically feel unsecure both inside and outside home that directly or directly impact the process of women empowerment as psychologically unsecure women will never be able to perform and contribute cent percent for their own growth and for the society. The paper discusses crime against women as a challenge to women empowerment using secondary sources of data.